2016
DOI: 10.1111/jpc.13314
|View full text |Cite
|
Sign up to set email alerts
|

Overweight, obesity and foot posture in children: A cross‐sectional study

Abstract: In children aged between 6 and 12 years, body mass does not appear to have an important bearing on static foot posture. Furthermore, the variables gender and age are of scant importance in determining foot posture in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…This greatly challenges the validity of the measures using this construct. At a minimum, these measures are reportedly influenced by the weight of the participants [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This greatly challenges the validity of the measures using this construct. At a minimum, these measures are reportedly influenced by the weight of the participants [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is important as previous studies have identified a relationship between increased BMI and flat feet in children using footprints . However, this finding has been refuted using the FPI measures . This has been queried previously, with footprints postulated to assess the spread of foot adipose with weight‐bearing rather than skeletal foot position …”
Section: Discussionmentioning
confidence: 99%
“…39,40 However, this finding has been refuted using the FPI measures. 29,41 This has been queried previously, with footprints postulated to assess the spread of foot adipose with weight-bearing rather than skeletal foot position. 13,29 Therefore, according to the current knowledge, the exclusive use of footprints to associate foot type and injuries or to assess foot structure is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The FPI was assessed with the children in a relaxed stance on a bench that was 50 cm tall. The same protocol that has been reported in other studies [ 6 , 49 , 50 , 51 ] was used. The FPI reflects the multisegmental nature of the posture of the foot in all three planes and does not require the use of specialized equipment.…”
Section: Methodsmentioning
confidence: 99%